High-definition tDCS of the motor cortex affects prefrontal and primary motor activity differently in young and older adults - Yasra Arif; Peihan J. Huang; Seth D. Springer; Hannah J. Okelberry; Jason A. John; Nathan M. Petro; Grant M. Garrison; Kennedy A. Kress; Kellen M. McDonald; Giorgia Picci; Tony W. Wilson (GeroScience, 2025)

Oscillatory Dynamics Serving Verbal Working Memory Differ in People with HIV and Are Linked To Disease Duration - Kellen M. McDonald; Seth D. Springer; Mikki Schantell; Ryan Glesinger; Lucy K. Horne; Hannah J. Okelberry; Jason A. John; Anna T. Coutant; Madelyn P. Willett; Hallie J. Johnson; Rachel K. Spooner; Tony W. Wilson (Journal of Neuroimmune Pharmacology, 2025)
Background Medical advances have greatly improved the quality of life and extended the longevity of people with HIV (PWH). However, many PWH still develop neurocognitive deficits even in the presence of effective viral suppression, with impairments in verbal working memory (VWM) being among the most common. While previous neuroimaging studies have demonstrated altered neural responses during VWM, the underlying temporal dynamics and their relation to clinical indices of HIV remain poorly understood. Hypothesis PWH will have altered neural oscillatory dynamics in brain regions supporting VWM compared to controls, above and beyond the effect of age, and these oscillatory differences will scale with clinical indices of HIV. Methods 166 participants (77 virally-suppressed PWH, 89 demographically-matched controls) completed a VWM task during magnetoencephalography, which was separated into encoding and maintenance phases. Whole-brain, mixed-model ANCOVAs were performed to assess the effects of HIV status on neural dynamics controlling for age. Results PWH performed significantly worse on the task compared to controls. During encoding, there was a significant interaction of group-by-time window, such that PWH had significantly weaker alpha/beta oscillations in the left inferior frontal, superior temporal, and anterior cingulate relative to controls. Further, weaker activity in the anterior cingulate scaled with increased disease duration. PWH also displayed weaker alpha/beta oscillations during maintenance in frontal, temporal, parietal, anterior cingulate, and cerebellar cortices. Conclusions PWH exhibited weaker task-related oscillatory activity during VWM, which was associated with disease duration in the anterior cingulate. Overall, these findings suggest that HIV modulates the neural dynamics underlying VWM, with progressive effects in some areas.

Non-native plant invasion after fire in western USA varies by functional type and with climate - Janet S. Prevéy; Catherine S. Jarnevich; Ian S. Pearse; Seth M. Munson; Jens T. Stevens; Kevin J. Barrett; Jonathan D. Coop; Michelle A. Day; David Firmage; Paula J. Fornwalt; Katharine M. Haynes; James D. Johnston; et al. (Biological Invasions, 2024)